2013
DOI: 10.1002/mar.20652
|View full text |Cite
|
Sign up to set email alerts
|

Scared Stiff? The Effectiveness of Threat Appeals in Counseling Services Advertising to High-Anxiety Students

Abstract: This exploratory study proposes and tests a theoretical model that analyzes threat appeals in regard to their effectiveness for high‐anxiety students, one of the major target groups for counseling services. In particular, affective and cognitive responses to a threat appeal advertisement and their effects on attitude toward the advertisement and behavior are examined. The results suggest that a strong threat appeal is not effective for counseling services but that positive emotions toward the advertisement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 89 publications
(191 reference statements)
1
6
0
Order By: Relevance
“…Also, contrary to previous empirical evidence (McLean & Anderson, ), female at‐risk gamblers did not significantly differ from male respondents in their self‐reported measure of evoked fear. Furthermore, in accordance with past empirical evidence on fear appeals in the drink‐driving context (Carey et al., ) or counselling services advertising (Krisjanous et al., ), findings form this study also suggest that in a problem gambling context, evoked fear did not significantly impact on help‐seeking intentions in male individuals. Overall, Study 2 results support the hypothesis that cognition is more important for both genders while processing fear appeals in a problem gambling context, as the direct impact of PS significantly and positively impacted help‐seeking intentions for both male and female at‐risk individuals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, contrary to previous empirical evidence (McLean & Anderson, ), female at‐risk gamblers did not significantly differ from male respondents in their self‐reported measure of evoked fear. Furthermore, in accordance with past empirical evidence on fear appeals in the drink‐driving context (Carey et al., ) or counselling services advertising (Krisjanous et al., ), findings form this study also suggest that in a problem gambling context, evoked fear did not significantly impact on help‐seeking intentions in male individuals. Overall, Study 2 results support the hypothesis that cognition is more important for both genders while processing fear appeals in a problem gambling context, as the direct impact of PS significantly and positively impacted help‐seeking intentions for both male and female at‐risk individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Krisjanous, Ashill, Eccarius, and Carruthers () suggested that mild threat appeals in counselling service advertising can be useful for high‐anxiety respondents who tend to engage in greater cognitive message processing of fear appeals. Overall, a recent meta‐analysis on fear appeal effectiveness confirmed that fear appeals depicting PS positively influenced intentions and behaviors in various health contexts and identified no circumstances under which these appeals backfired or led to undesirable consequences (Tannenbaum et al., ).…”
Section: The Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes have long been considered to be predictive of perceptions and behaviors (Ajzen ), and are often posited as a mediating variable through which advertising exerts its effects (MacKenzie, Lutz, and Belch ). Krisjanous et al () found that attitude mediates the relationship between affective response toward advertisements and greater information‐seeking intention. Similarly, involvement is a critical variable in the study of advertising effectiveness and has an important influence in the consumer‐decision‐making process (Park and Hastak ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…This is consistent with research in public health campaigns, which finds that increases in message relevance (e.g., through increased “threat” or “fear”) can result in more damaging behavior under low levels of efficacy (Rippetoe & Rogers, ; Wolburg, ). It has been argued that this happens because people resort to defensive mechanisms, such as denial, to cope with the “hopeless” situation (Krisjanous, Ashill, Eccarius, & Carruthers, ; Witte, ).…”
Section: Discussionmentioning
confidence: 99%